Alagille syndrome and liver: an adult case report - Oussama Kharmach; Mohamed Borahma; Fatima-Zohra Ajana (Egyptian Liver Journal, 2023)
Abstract Background Alagille syndrome is a rare autosomal-dominant disorder, representing 10 to 15% of the causes of neonatal cholestasis with no gender predominance. The diagnosis is based on the association of liver, heart, eye, skeleton abnormalities, and characteristic facial appearance. Case presentation An 18-year-old male patient, with a family history of benign recurrent intrahepatic cholestasis in a brother, was diagnosed at birth with bile duct paucity. He consulted in adulthood for cholestatic jaundice and pruritus. Physical exam found cutaneous jaundice, particular face, skeletal abnormality of fingers, posterior embryotoxon, and splenomegaly. An echocardiogram found cardiovascular abnormalities. The diagnosis of Alagille syndrome was made in front of five major criteria. A liver biopsy revealed a cirrhosis liver. Upper gastrointestinal endoscopy revealed grade II esophageal varices of portal hypertension. Laboratory tests revealed bicytopenia related to hypersplenism, hypoferritinemia, cytolysis with cholestasis, high bilirubin levels, low prothrombin time, hypoalbuminemia, decreased factor V activity, and hypocholesterolemia. The patient had vitamin K supplementation and was put on ursodeoxycholic acid, propranolol for the liver disease, a high protein hypercaloric diet for malnutrition, vitamin D supplementation and bisphosphonate for the osteoporosis, therapeutic abstention with monitoring for the asymptomatic cardiac disease. After a year of treatment, the patient had an overall health status improvement. Abdominal ultrasound found liver nodules. A biliary MRI showed a multinodular liver. The complement by CT hepatic angiography did not show any nodules while the MRI angiography revealed multiple dysplastic nodules. A liver biopsy was performed and found regenerative nodules. Conclusion The treatment of Alagille syndrome is based on managing the cholestasis and its complications, especially pruritus because it can have a significant impact on quality of life. Due to the complexity of presentation and multi-organ involvement, management of cases with Alagille syndrome should be done by a multidisciplinary team. Liver disease is responsible for morbidity while cardiac disease is a mortality risk factor in this population.